A STUDY OF TEACHING SPEAKING STRATEGY USED IN FAJAR ENGLISH COURSE PARE, KEDIRI - Durrotun Nafisah; Maskhurin Fajarina (Lembaga Pengembangan Kinerja Dosen, 2023)
Speaking is one of the important skills that must be learned by anyone who wants to master English. In mastering speaking skills, it is necessary to use several strategies. Researchers compiled this thesis with the aim of knowing how the strategies used by tutors in teaching speaking , and students' responses to the strategies used by tutors helped them improve students' speaking skills at Fajar English Course, Pare, Kediri. The research method used by the researcher is a qualitative descriptive method. Researchers obtained data by observing one speaking class program, namely Mentari class. The researcher also interviewed three tutors in Mentari class and two students in Mentari class. Finally, the researcher collected the documentation obtained from the observations in class. The data were analyzed by organizing the data obtained by the researcher. The findings of this study indicate that the strategies applied by tutors are conversation, story telling, presentation, debate, breaking news, and speech.The reason the tutor uses this strategy is because the strategy is considered a fun strategy, gives students confidence to dare to speak in public, motivates students not to be afraid of making mistakes when speaking, and from speaking practice students also gain new knowledge. For students who have difficulty in learning speaking, the tutor encourages and motivates them to practice more speaking both inside and outside the classroom. Because every difficulty in the process of learning speaking is considered to be easy to overcome with a lot of practice.